1984
DOI: 10.1111/j.1365-2125.1984.tb02402.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of ibopamine, a dopamine pro‐drug, on renal function in normal subjects.

Abstract: The effects of two single oral doses of ibopamine (150 and 600 mg) on heart rate, blood pressure, urine flow, sodium, potassium and creatinine excretion were studied in normal volunteers. No significant change was observed in urine flow, sodium, potassium or creatinine excretion at either dose. No significant change was observed in heart rate or blood pressure except that systolic blood pressure was transiently elevated after the 600 mg dose (P less than 0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…In healthy volunteers renal haemodynamic effects of ibopamine have been assessed only by calculation of endogenous creatinine clearances (Harvey et al, 1984;Incerti et al, 1986;Stefoni et al, 1981), with the exception of a small study by Britton who measured ERPF (Britton et al, 1986). A pronounced increase in creatinine clearance with a dose of 50 mg was found in an acute open study by Incerti et al (1986).…”
Section: Discussionmentioning
confidence: 99%
“…In healthy volunteers renal haemodynamic effects of ibopamine have been assessed only by calculation of endogenous creatinine clearances (Harvey et al, 1984;Incerti et al, 1986;Stefoni et al, 1981), with the exception of a small study by Britton who measured ERPF (Britton et al, 1986). A pronounced increase in creatinine clearance with a dose of 50 mg was found in an acute open study by Incerti et al (1986).…”
Section: Discussionmentioning
confidence: 99%
“…When the dose was in creased by 50 mg every second day, there was a further increase in diuresis, along with a 2% decrease in body weight on day 10 and day 12, respectively [52], Also, Incerti et al [53] found an increase in diuresis and so dium and potassium excretion with the 50-mg dose. Stefoni et al [34] The absence of significant diuretic effects observed by Harvey et al [49] and Ren et al [4] could be due to the fact that when high doses are used, the stimulation of a-adrenergic receptors compensates the favorable do paminergic effect on the renal function. Verga et al [54] demonstrated an increase in the furosemide-induced diuresis, sodium and potassium excretion following the ad ministration of 100 mg ibopamine.…”
Section: In Volunteersmentioning
confidence: 96%
“…Results of the double-blind, placebo-con trolled studies by Ren et al [4] and Harvey et al [49] show that single-dose ibopamine does not produce any significant effect on diuresis, sodium or potassium excretion and creatinine clearance. The authors treated volunteers with doses ranging between 100 and 600 mg. Cicchetti et al [50], Melloni et al [35] and Britton et al [51], on the con trary, found a 20% (50-200 mg) and 60% (600 mg) increase in diuresis, respectively, also with double-blind experimental proto cols.…”
Section: In Volunteersmentioning
confidence: 99%
“…The reason for the apparent insensitivity of healthy persons is not clear (55). Glomerular filtration rate (GFR) was found to be increased in patients after 7 days of ibopamine (50 mg twice daily) treatment (29).…”
Section: Bopaminementioning
confidence: 99%
“…Volume diuresis and natriuresis is observed after ibopamine in patients with chronic heart failure (29,73) but not in healthy volunteers (55,97). The reason for the apparent insensitivity of healthy persons is not clear (55). Glomerular filtration rate (GFR) was found to be increased in patients after 7 days of ibopamine (50 mg twice daily) treatment (29).…”
Section: Bopaminementioning
confidence: 99%